2017
DOI: 10.1088/2053-1583/aa70fa
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry forbidden morphologies and domain boundaries in nanoscale graphene islands

Abstract: The synthesis of graphene nanoislands with tailored quantum properties requires an atomic control of the morphology and crystal structure. As one reduces their size down to the nanometer scale, domain boundary and edge energetics, as well as nucleation and growth mechanisms impose different stability and kinetic landscape from that at the microscale. This offers the possibility to synthesize structures that are exclusive to the nanoscale, but also calls for fundamental growth studies in order to control them. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Note that similar bright objects were also observed on graphene islands synthesized by temperature programmed growth (TPG) on the Ni(111) surface from ethylene and propylene 17,18 . In our previous study 19 , we considered TPG synthesis of graphene on Ni(111) and assigned the bright features in STM images with nickel defects, i.e.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Note that similar bright objects were also observed on graphene islands synthesized by temperature programmed growth (TPG) on the Ni(111) surface from ethylene and propylene 17,18 . In our previous study 19 , we considered TPG synthesis of graphene on Ni(111) and assigned the bright features in STM images with nickel defects, i.e.…”
Section: Introductionmentioning
confidence: 61%
“…In the present work, graphene was synthesized from propylene on the Ni(111) surface by both CVD and TPG methods. In both cases, identical objects similar to the defects described in [12][13][14][15][16][17][18][19] were found in STM images. We performed a DFT simulation of the transition from one structure (nickel in monovacancies) to another structure (nickel in bivacancies) and found that the main nickel defect in graphene is the nickel atom in the carbon bivacancy.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Luo et al [10] carried out a series of graphene growth on Cu (1 1 1) surfaces at the fixed CH 4 flow rate (0.5 standard cubic centimetres per minute (sccm)) and different H 2 flow rates (15,20,25,30,35,40,45, and 50 sccm, respectively). As shown in figures 2(a)-(h), the graphene morphology transforms from a fragmentary, to a fractal, and further to a compact domain with increasing H 2 flow rate.…”
Section: Morphology Evolution Of Graphene With Hydrogen Flow Ratementioning
confidence: 99%
“…Great theoretical efforts have been devoted to disclosing various mechanisms during CVD of graphene [21,22], such as initial nucleations [23][24][25], carbon sources [26], growth intermediates [27,28], edge structures [29][30][31][32], growth kinetics [33][34][35], vacancy kinetics [36][37][38], and domain morphologies [39][40][41][42][43][44]. Compared to ab initio calculations, kinetic Monte Carlo (kMC) simulations are able to provide atomistic level insights into the kinetics of the growth process with much larger time scale and length scale [27,32,34,43,44].…”
Section: Introductionmentioning
confidence: 99%